Cinema mato-grossense contemporâneo : estudo a partir de quatro longas produzidos entre 2015 e 2020 - Passos, Naiara Cristina Gonçalves Rocha (2022)
This work aims to present and discuss the production conditions and characteristics of cinema produced in the state of Mato Grosso, Brazil. Starting with the turn, for the second decade of the 21st century to the present day. From the analysis of four feature films produced between the years 2015 and 2020 in the region. The four films in question, Loop, by Bruno Bini; Shangrilá, by Severino Neto; Sísmico, a documentary also by the filmmaker Severino Neto and Luciene, a fictional documentary by Juliana Curvo. All carried out through public notices linked to the Audiovisual Sector Policy, whose funding involved the state (of Mato Grosso) and federal public authorities. The research, in agreement with Sérgio Santos (2017), seeks to portray the Fundo Setorial do Audiovisual (FSA) as a new reality of promotion in relation to other public policies in force in Brazil, and reveals its influence on the general characteristics of cinematographic production in Brazil. State of Mato Grosso, which until then was constituted historically and mostly by advertising films (governmental, business) and anthropological records. To fulfill these questions, the research is based both on classical theoretical studies developed on the activity of film analysis and on the available bibliography on film production in Mato Grosso, on the one hand, and on the theoretical thought of Political Economy of Communication, on the other. , to align production and context in the objectives of this work.